Penerapan Teknologi Sistem Informasi untuk Mendukung Informasi dan Promosi pada Kaliwungu Printing - Edy Siswanto; Arie Atwa Magriyanti; Achmad Bachtiari (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study is motivated by the declining revenue of Kaliwungu Printing every month, which is caused by the inconsistency in product promotion. As a result, the lack of regular and comprehensive promotional efforts has led to limited public awareness of Kaliwungu Printing. The purpose of this research is to develop a structured and comprehensive promotional tool to showcase the products offered by Kaliwungu Printing. This research employs a qualitative method to obtain accurate and relevant data. Data collection techniques include observation, interviews, and questionnaires. The respondents consist of media experts, content experts, and a group of five employees from Kaliwungu Printing. The validity of the data is measured using the rating scale method proposed by Sugiyono. The results of the study show a score of 30 from media experts, 36 from content experts, and an 84% validity rate from the group assessment. Based on the overall evaluation indicators, these results fall into the